Encyclopedia of ancient literature [ - Cook, James Wyatt , 1932- (Gale virtual reference library, 2008)
Features numerous entries covering the literary works, writers, and concepts of the ancient world, from the beginnings to approximately 500 CE. Ranging from ancient Greece and Rome to China, Egypt, Japan, India, Persia, Babylonia, the Hebrew world, and more, provides students with an extensive overview of this period of literature